Increasing the Social Activity of Students in the Process of English Language - Ilxom Qizi, Samiyeva Zuhra (International Journal of Culture and Modernity, 2022)
The article covers the issues of knowledge, skills and abilities of future teachers, the orientation of professional skills to innovative pedagogical processes and the creation, mastering, implementation of pedagogical innovations, the definition of their pedagogical skills and innovative competence.